2006
DOI: 10.1017/s1355617706060954
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cataract surgery on neuropsychological test performance: A randomized controlled trial

Abstract: Recent cross-sectional studies have reported strong associations between visual and cognitive function, and longitudinal studies have shown relationships between visual and cognitive decline in late life. Improvement in cognitive performance after cataract surgery has been reported in patients with Mild Cognitive Impairment. We investigated whether improving visual function with cataract surgery would improve neuropsychological performance in healthy older adults. A randomized clinical trial of cataract surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…In this journal, Anstey et al (2006) reported the results of a potentially important clinical study on the effect of cataract removal on the cognitive performance of older adults. Unfortunately, because of inappropriate data analyses, some reported results are meaningless.…”
Section: Letter To the Editormentioning
confidence: 99%
“…In this journal, Anstey et al (2006) reported the results of a potentially important clinical study on the effect of cataract removal on the cognitive performance of older adults. Unfortunately, because of inappropriate data analyses, some reported results are meaningless.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The only significant baseline difference in Anstey et al (2006), that in visual acuity, had a p-value of .03, but this was one out of eight tests for baseline differences (see their Table 1). So the risk of a type I error caused by multiple testing was considerable.…”
mentioning
confidence: 97%
“…We hope that our commentary will contribute to a further improvement in the use of advanced statistics in neuropsychology. Anstey et al (2006) reported the effects of cataract surgery on neuropsychological test performance in an RCT. They used repeated measures ANOVA to test for group by time interaction, adjusting for two covariates: age and baseline visual acuity.…”
mentioning
confidence: 99%
“…argues that the use of ANCOVA in Anstey et al (2006) is invalid. Based on quotes in Winer (1971), he claims that covariates cannot be used to adjust interaction terms involving within-subject variables.…”
mentioning
confidence: 99%
“…Based on quotes in Winer (1971), he claims that covariates cannot be used to adjust interaction terms involving within-subject variables. Because the withinsubject variable in Anstey et al (2006) is time, he concludes that the results involving Time 3 Group interaction coefficient are invalid and consequently all analyses need to be re-done.…”
mentioning
confidence: 99%